2015
DOI: 10.1002/cphc.201500938
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Polarization Electron‐Nuclear Double Resonance Spectroscopy

Abstract: Magnetic nuclei in the proximity of a paramagnetic center can be polarized through electron-nuclear cross-polarization and detected in electron-nuclear double resonance (ENDOR) spectroscopy. This principle is demonstrated in a single-crystal model sample as well as on a protein, the β2 subunit of E.coli ribonucleotide reductase (RNR), which contains an essential tyrosyl radical. ENDOR is a fundamental technique to detect magnetic nuclei coupled to paramagnetic centers. It is widely employed in biological and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…An alternative method to obtain the angle θ is the use of orientation-selected HF ENDOR spectroscopy, however the low radical yield of D 6 -NH 2 Y 731 • unfortunately has so far prevented these experiments. We are in the process to introduce CP-edited ENDOR 71 for 2 H nuclei, which will potentially facilitate the analysis of 2 H-HF ENDOR spectra. Preliminary 94 GHz 2 H CP-ENDOR data (not shown) on H 6 -ND 2 Y 731 •-α2 seem entirely consistent with the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method to obtain the angle θ is the use of orientation-selected HF ENDOR spectroscopy, however the low radical yield of D 6 -NH 2 Y 731 • unfortunately has so far prevented these experiments. We are in the process to introduce CP-edited ENDOR 71 for 2 H nuclei, which will potentially facilitate the analysis of 2 H-HF ENDOR spectra. Preliminary 94 GHz 2 H CP-ENDOR data (not shown) on H 6 -ND 2 Y 731 •-α2 seem entirely consistent with the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Again, we suggest that the absence of the negative peak is due to a cancellation resulting from sample inhomogeneities, which are not considered in the analytical treatment, as we neglect any off-resonance effects. Recent analysis of powder patterns [33,37] indicated that negative peaks disappear in the presence of such inhomogeneities. Nevertheless, the overall agreement between different theoretical predictions and the experimental data is striking and not obvious, as the analytical prediction of intensities (Table 3) does not explicitly calculate a time evolution of the density operator during the spin lock, whereas the numerical simulation does.…”
Section: Comparison With the Experimental Resultsmentioning
confidence: 99%
“…47,48 Importantly, all three of these time domain DNP transfers can be implemented with chirped frequency microwave irradiation, rather than square, hard pulses. Such frequency-swept strategies are not only robust to microwave field inhomogeneity but also can be readily implemented with existing frequency-agile gyrotrons.…”
mentioning
confidence: 99%
“…eNCP (Figure 3c) is another promising time domain DNP experiment 47,48 and could be implemented with readily available frequency-agile gyrotron microwave sources. Large hyperfine couplings present in a direct-transfer eNCP experiment result in differing effective fields between the and spin states of the nuclei and electrons The matching condition for eNCP is given by eq 6, where ν Sα eff and ν Sβ eff are the effective fields of the and electrons, respectively, and ν Iα eff and ν Iβ eff are the effective fields of the and nuclei, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation